Embedding Two of the 4Ms Into the Electronic Health Record: One Health System’s Journey Towards Systemwide Spread of Age-Friendly Care - Anna-Rae Montano PhD, RN, MEDSURG-BC, OCN; Christine Waszynski DNP, APRN, GNP-BC (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2025)
The purpose of this article is to describe 2 quality improvement projects aimed at embedding 2 of the 4Ms into the electronic health record for system-wide spread of Age-Friendly care. The 2 projects described in this case study serve as exemplars for the future implementation and sustainability of 4Ms care. Rapid-cycle quality improvement projects, via the Plan, Do, Study Act model, focused on the 4Ms were conducted by interprofessional teams to integrate clinical decision support for clinicians within the electronic health record. Project Senior Care Review for Evaluating and Eliminating Non-essential and potentially inappropriate medications (SCREEN) embedded a geriatric medication screen into the ordering panels of the top medications identified as being prescribed to older patients potentially inappropriately. Project Predictive Real-time Evaluation of Delirium in Clinical Therapy (PREDICT) embedded a delirium prediction rule in the electronic health records to guide clinicians to implement delirium mitigation interventions on patients at risk of developing or experiencing delirium. Outcomes were evaluated descriptively utilizing data and reports generated by the electronic health record. Embedding non-interruptive and actionable clinical decision support in the electronic health record supported the rapid spread of Age-Friendly care across a 7-hospital system. The 4Ms can be embedded into existing workflows through novel implementation of best practices by leveraging the electronic health record. By embedding 2 of the 4Ms into existing workflows and creating non-disruptive, actionable clinical decision support within the electronic health record, clinicians have the tools to implement Age-Friendly care within the 4Ms framework. Additional projects aimed at embedding the other Ms are underway, and long-term outcomes are being evaluated.